THE EFFECT OF ELECTRONIC SERVICE QUALITY, PRODUCT, PRICE, PROMOTION ON CUSTOMER SATISFACTION (CASE STUDY ON CUSTOMER ONLINE STORES LAZADA.CO.ID JAKARTA) - Nawangsari, Sri; Clara, Dhea Ajeng; Wibowo, Eri Prasetyo (APTIKOM Journal on Computer Science and Information Technologies, 2020)
Satisfaction This research aims to know the effect of electronic service quality, product, price, promotion on customer satisfaction in the Lazada.co.id online store customers in Jakarta. Electronic service quality, product, price, promotion is a things into consideration and provide value to customers in choosing an online store as a destination shopping. In this study the author uses an online questionnaire method against 235 respondents or Lazada.co.id customers. Then conducted an analysis of the data obtained in the form of a descriptive analysis, quantitative analysis include the assay validity, reliability test, test of goodness of fit, and the analysis of the model of measurement SEM (Structurak Equation Modelling) using Software AMOS 22.0. From a study of 235 respondents, results of the study indicate significant influence between the influence of the interactions in five variables, namely (1) Electronic Service Quality affects Satisfaction, (2) Product affect Satisfaction, (3) Price affect Satisfaction, (4) Promotion affect Satisfaction